2021
DOI: 10.1007/s10964-021-01549-2
|View full text |Cite
|
Sign up to set email alerts
|

Service, Activism, and Friendships in High School: A Longitudinal Social Network Analysis of Peer Influence and Critical Beliefs

Abstract: Scholars acknowledge that friends shape youth civic engagement, but the relative contribution of peer influence and critical beliefs to civic behaviors has yet to be disaggregated. Informed by sociopolitical development and critical consciousness theories, the present study used longitudinal social network analysis to examine peer socialization and adolescents’ awareness of systemic inequities in relation to participation in service and activist activities at a high school serving primarily low-income Latinx y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Peer pressure emerged as a major determinant of youth political behavior in various contexts, including social media and real-world networks (Renstrom et al, 2021;Park et al, 2017;Bergan et al, 2022;Wang et al, 2018;McCabe, 2018;Wegemer, 2021;Goel et al, 2010;Braha et al, 2017). However, when measuring conformity, social desirability bias and self-reporting bias should be considered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peer pressure emerged as a major determinant of youth political behavior in various contexts, including social media and real-world networks (Renstrom et al, 2021;Park et al, 2017;Bergan et al, 2022;Wang et al, 2018;McCabe, 2018;Wegemer, 2021;Goel et al, 2010;Braha et al, 2017). However, when measuring conformity, social desirability bias and self-reporting bias should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…As Table 2, investigates the influence of peer pressure on youth political behavior, concentrating on civic engagement in service and activist activities, and perceptions of systemic inequities (Wegemer, 2021). It indicates that youths' peers can influence their participation in service activities, highlighting that peer socialization influencing such behaviors.…”
Section: Themes 3: Peer Pressurementioning
confidence: 99%
“…A second limitation is that the ERGMs examined the presence of homophily cross‐sectionally and were unable to disaggregate processes that contributed homophily among students. Longitudinal social network methods (e.g., SIENA) have recently been applied to youth civic engagement to deepen the understanding of peer influence and friendship selection that might lead friend groups to become similar on civic behaviors and beliefs (Wegemer, 2022). Clarifying network processes could advance the interactional approaches to civic education (Passe et al, 2018) and may lead to novel high school policies and practices that effectively leverage social mechanisms to support adolescents' civic engagement and sociopolitical development.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have long recognized that adult friendship groups are more politically homogenous than one would predict by chance (Verbrugge, 1977); yet, research on youth is lacking, despite the importance of adolescent experiences in shaping political attitudes throughout adulthood (Russo & Stattin, 2017). Building on an emerging line of research that leverages social network concepts and methodologies to examine the relational features that underlie youth civic engagement (e.g., Kornbluh et al, 2023; Wegemer, 2022), the present work investigates adolescents' potential affinity for peers who have similar levels of service, activism, and awareness of inequities at a high school that serves primarily low‐income Latiné youth. Below, relevant literature is introduced by describing the role of high school activities in homophilous sorting, and then, with attention to the experiences of Latiné youth, sociopolitical development theory (Watts et al, 2003) is utilized to differentiate activism from service and to highlight the importance of awareness of inequities within adolescent friendship networks.…”
Section: Introductionmentioning
confidence: 99%
“…Critical consciousness, inclusive of three main dimensions of critical action, agency, and reflection, is social by nature, as each component involves thinking with, talking with, and acting with others towards shared and co-constructed social justice goals [9]. Research has suggested that adolescents can influence each other's sociopolitical engagement through their friendships (e.g., [10][11][12][13][14]), and associations between youths' activism and mental health may be moderated by relationships with peers [15,16]. Peer groups are an important developmental context and the characteristics of adolescents' friends can…”
Section: Introductionmentioning
confidence: 99%